Primary B-cell MALT lymphoma of the palate: A case report and distinction from benign lymphoid hyperplasia (pseudolymphoma) - Manveen, Jawanda Kaur (Medknow Publications & Media Pvt Ltd, 2012)
Diagnosis of palatal swellings is a challenge. Benign and malignant tumors may be misinterpreted as lesions of inflammatory origin. We present a case of B-cell non-Hodgkin lymphoma on the palate of a 40-year-old male. A number of factors can make the diagnosis of oral lymphoma difficult. Many lymphomas are extranodal, there is usually a prominent superimposed nonspecific inflammatory response and thus they mimic benign lymphoid hyperplasia. It is important for the pathologist to be familiar with features that distinguish benign from malignant lymphoid proliferations.